Real-world safety and effectiveness of nivolumab in patients with cancer of unknown primary: results from a nationwide post-marketing surveillance in Japan - Akira Kawasaki; Akito Kakuuchi; Ayumi Akamatsu; Misato Nakanishi; Chikara Honda (International Journal of Clinical Oncology, 2026)
Abstract Background Cancer of unknown primary (CUP) is associated with poor prognosis. In December 2021, nivolumab was approved in Japan for the treatment of CUP based on a small phase II trial. This post-marketing surveillance (PMS) evaluated the real-world safety and effectiveness of nivolumab in Japanese patients with CUP. Methods This prospective, observational, PMS enrolled patients with CUP who initiated nivolumab between April 2022 and June 2023 at 66 institutions. Patients were observed for 6 months. Safety outcomes were treatment-related adverse events (TRAEs), and effectiveness outcomes included overall response rate (ORR) and overall survival (OS). Analyses were descriptive. Results Among 151 patients in the safety set, the median age was 70 years and 79.5% had an Eastern Cooperative Oncology Group performance status (PS) 0–1. Any grade and Grade ≥ 3 TRAEs occurred in 25.2% and 11.9% of patients, respectively. Frequently reported TRAEs included interstitial lung disease (3.3%), hepatic function abnormal (2.6%), and hypothyroidism (2.6%). There was one TRAE (neutropenia) resulting in death. In the effectiveness set ( n = 144), the ORR was 21.5%. ORR was higher in patients without prior systemic therapy (25.4% vs. 18.2%) and in those with lymph node-only involvement (36.6% vs. 15.5%). The 6-month OS rate was 71.0%, and median OS was not reached. The 6-month OS rates were greater in patients with PS 0–1 and lymph node-only involvement. Conclusions Nivolumab was tolerated in patients with CUP in routine practice in Japan, with no new safety concerns, and indicated antitumor activity consistent with clinical trial results. Trial registration Japan Registry of Clinical Trials (jRCT2041240121).